The role of stigma in impeding implementation of harm reduction services in San Francisco - Christopher F. Akiba; Cariné E. Megerian; Esther O. Chung; Terry Morris; Lynn D. Wenger; Leslie W. Suen; Barrot H. Lambdin; Alex H. Kral (SSM: Qualitative Research in Health)
The United States continues to face an epidemic of drug overdose deaths among people who use drugs (PWUD). Harm reduction services are efficacious interventions that reduce overdose deaths and improve the health of PWUD. For decades, San Francisco has remained at the vanguard of the adoption, implementation, and sustainability of harm reduction programs. During a time of national urgency in 2023, we conducted a qualitative study interviewing leaders, managers, and frontline staff at 10 community-based organizations providing harm reduction services in San Francisco. We analyzed in-depth interview data using Reflexive Thematic Analysis. Participants described feeling that PWUD, providers of harm reduction services, and the services themselves became highly stigmatized at the political and community levels. Multi-level stigma was exacerbated by the city's social and economic conditions including extreme income inequality and gentrification, giving rise to public drug use and open-air drug markets. Multi-level stigma was upheld by a system of anti-harm reduction rhetoric and misinformation from public officials, leading to its politicization and insufficient funding for organizations providing harm reduction services. These barriers resulted in harm reduction worker self-censorship and staff trauma, burnout, and turnover, leading to program implementation challenges and ultimately harming organizations' abilities to improve the health of PWUD. Organizations mitigated barriers through mutual aid but only to a degree. Targeting stigma directly may help to address implementation challenges over the long term and lead to additional, sufficient, and sustained funding needed to ensure adequate and stable service provision.